2000
DOI: 10.1007/s003300000316
|View full text |Cite
|
Sign up to set email alerts
|

Altered energy metabolism after myocardial infarction assessed by 31 P-MR-spectroscopy in humans

Abstract: The value of 31P-magnetic resonance spectroscopy (MRS) as a possible tool to distinguish viable from non-viable tissue after myocardial infarction was analysed in humans. Fifteen patients 3 weeks after anterior myocardial infarction were studied with breath-hold cine MRI and 3D-CSI MRS (1.5 T system). 31P-spectra were obtained from infarcted as well as non-infarcted myocardium (voxel size 25 cm3 each). Gold standard for viability was recovery of regional function, as determined by a control MRI 6 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Another problem is the impossibility to calculate PCr/ATP ratios from voxels, which do not contain any PCr signal amplitudes. Authors Beer et al [64] therefore used the signal-to-noise ratio of ATP as an indirect measurement for ATP content in patients with anterior myocardial infarction. Thus, they observed a significant reduction of ATP in patients with scar tissue.…”
Section: Normal Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another problem is the impossibility to calculate PCr/ATP ratios from voxels, which do not contain any PCr signal amplitudes. Authors Beer et al [64] therefore used the signal-to-noise ratio of ATP as an indirect measurement for ATP content in patients with anterior myocardial infarction. Thus, they observed a significant reduction of ATP in patients with scar tissue.…”
Section: Normal Valuesmentioning
confidence: 99%
“…neither PCr nor ATP peaks detectable for the anterior region. This patient showed no recovery of regional function after revascularization and was classified as having non-viable tissue; modified according to [64] Multiple sclerosis Another multisystemic neurological disease with a suspected cardiac involvement is MS. Whether MS, in addition to CNS involvement, structurally affects the heart is under debate [79,80].…”
Section: Myopathiesmentioning
confidence: 99%
“…The signal-to-noise ratio (SNR) of PCr and γ-ATP were calculated also using "AMARES" [19]. Noise was determined via the standard deviation of the last 100 points of the FID signal [6].…”
Section: P-mr-spectroscopymentioning
confidence: 99%
“…Most of the studies have shown reductions of energy metabolites [4], which correspond to fixed defects in nuclear studies [5] or persistent wall motion abnormalities (WMA), despite revascularization procedures [6]. However, these results are conflicted by other studies, which show only minor or no changes of energetics after MI [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the myocardial PCr/ATP ratio determined using 31 P-MRS is used to evaluate patients with cardiac disease [6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%